A 2D parallel high-order sliding and deforming spectral difference method. (5th November 2016) - Zhang, Bin; Liang, Chunlei; Yang, Jingjing; Rong, Yongwu
Highlights: A new method is developed for flow problems on sliding/deforming meshes. This method dramatically reduces mesh skewness due to rotating boundaries. This method is high-order accurate for both inviscid and viscous flows. This method is scalable for parallel computing. This method is more accurate than deforming-only ALE method. Abstract: In this paper, we present a novel parallel high-order sliding and deforming spectral difference (SD 2 ) method for solving the two-dimensional compressible Navier–Stokes equations on unstructured quadrilateral grids. In the SD 2 method, an arbitrary Lagrangian–Eulerian (ALE) approach is combined with a novel sliding interface approach to separately handle rotational and translational motions on a dynamic grid. The SD 2 method is shown to be capable of completely removing grid skewness caused by rotating boundaries to improve solution qualities. The SD 2 method is verified as high-order accurate and is scalable for parallel computing on a distributed-memory computer. The SD 2 method is also proven to be more robust and more accurate than deforming-only ALE approach for problems involving large-amplitude rotating motions.